Digital technologies and sustainable development: an insight from corporate sector - Javeed, Sohail Ahmad; Yang, Xiaoping; Latief, Rashid; Ong, Tze San; Jinglu, Li (John Wiley and Sons Ltd, 2025)
The excessive utilization of industrial output has drawn significant attention from authorities toward sustainable development. Given the substantial environmental challenges posed by the industrial sector, sustainable development has emerged as a paramount concern for scholars and organizations alike. In this context, considerable emphasis has been placed on the significance of digitization. Digital technologies, particularly blockchain technology (BCH) and digital finance (DF), are transforming the landscape of business and the economy, facilitating corporate sustainable development (CSD), enhancing corporate social practices, and fostering green innovation. Through the application of various econometric strategies using the Chinese business sector as a sample of the study, we found that BCH effectively promotes green innovation and corporate social activities. Additionally, our analysis underscores the critical role of DF in advancing corporate social practices and green innovation. Notably, we highlight the importance of human capital as a moderating factor that strengthens the relationships between BCH and CSD, as well as between digital finance and CSD. This study offers novel insights into ways, digital technology can enhance corporate sustainability practices and presents a framework that may be of significant utility to policymakers and decision-makers.